Homogeneous (α, β)-spaces with positive flag curvature and vanishing S-curvature. (November 2015) - Xu, Ming; Deng, Shaoqiang
Abstract: We give a complete classification of homogeneous ( α, β ) -metrics with positive flag curvature and vanishing S-curvature.